The Influence of Internal Communication, Work Discipline, and Teamwork on Employee Performance at the Regional House of Representatives Office in Gowa Regency - Fitrah Indah (Green Publisher Indonesia, 2024)
This study aims to determine and analyze the effect of internal communication on employee performance, work discipline on employee performance and teamwork on employee performance at the Office of the Regional House of Representatives of Gowa Regency. This type of research is quantitative research with a sample of 43 respondents using a questionnaire as data collection. The analysis used is Multiple Linear Regression Analysis using the SPSS V.24 application. The results showed that: 1. Internal communication has a positive and significant effect on employee performance, 2. Work discipline has a positive and insignificant effect on employee performance, and 3. Teamwork has a positive and significant effect on employee performance.